Rethinking Radical Politics and Ethics - Han-yu Huang (Appareil)
Alain Badiou’s coming to the forefront of the academic debates on the ontological status of Being, political subjectivity, universality, and so on, deserves special attention in an age permeated by disillusionment, cynicism, apathy, or “announcements of ending”: summarily, the post-political age. This is also an age when “(hyper)connectivity” with and openness to the Other becomes the dominant currency but radical politics and ethics reach their deadlock, if not demise. Drawing on Badiou’s conceptions of subtraction, universal singularity, and the subject loyal to the truth procedure, my proposed paper will critically look at whether contemporary multiculturalism and “society of enjoyment” end up at nothing but relativist ideology, victimization of man, false image of satisfaction and transgression, and, hence, submission to the status quo more than ever. The final part will examine the possibility of supplementing Badiou’s universalizing project with Žižek’s recent conceptualization of the inhuman and ethical violence and reinvigorating ethico-politically authentic emancipatory thinking.